RIFM fragrance ingredient safety assessment, β-methylphenethyl alcohol, CAS Registry Number 1123-85-9. (December 2017) - Api, A.M.; Belsito, D.; Botelho, D.; Browne, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; Francis, M.; et al.
Highlights: β-Methylphenethyl alcohol safety assessment based on RIFM's criteria. Safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read across and/or TTC.